1989
DOI: 10.1037/0735-7028.20.5.283
|View full text |Cite
|
Sign up to set email alerts
|

Dual relationships between therapist and client: A national study of psychologists, psychiatrists, and social workers.

Abstract: 4,800 psychologists, psychiatrists, and social workers were surveyed (return rate = 49%) to examine attitudes and practices regarding dual professional roles, social involvements, financial involvements, and incidental involvements. Half of the Ss rated the degree to which each behavior was ethical; the other half reported how often they engaged in each behavior. A majority believed dual role behaviors to be unethical under most conditions; most reported that they had rarely or never engaged in the behaviors. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
232
6
7

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(267 citation statements)
references
References 30 publications
20
232
6
7
Order By: Relevance
“…Furthermore, not only were these gifts not discussed (at least according to the client reports), but neither was Emma's admitted use of the gifts as a means of expressing feelings she was uncomfortable verbalizing in the therapy nor her sense of the gifts as a way she could "repair" herself via behavior rather than therapeutic discussion. Echoing earlier theorists' concerns and contradicting other researchers' suggestions about gifts in therapy (Borys & Pope, 1989;Freud, 1917Freud, /1963Gerson & Fox, 1999;Glover, 1955;Hundert, 1998;Knox et al, 2003;Kritzberg, 1980;Langs, 1974;Lewinsky, 1951;Pope et al, 1987;Ruth, 1996;Simon, 1989;Spandler et al, 2000;Talan, 1989), Dr. E reportedly did not address Emma's motivations for giving the gifts, the nature of what they communicated, the prominent role they began to take in her therapy, nor their effect on the therapy process and relationship. Perhaps, following a more intersubjectivist approach (e.g., Atwood & Stolorow, 1984;Hahn, 1998;Stolorow & Atwood, 1996), Dr. E may have sought to affirm and accept Emma by accepting her gifts (although we cannot know this without having talked to the therapist).…”
Section: Many-gift Examplementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, not only were these gifts not discussed (at least according to the client reports), but neither was Emma's admitted use of the gifts as a means of expressing feelings she was uncomfortable verbalizing in the therapy nor her sense of the gifts as a way she could "repair" herself via behavior rather than therapeutic discussion. Echoing earlier theorists' concerns and contradicting other researchers' suggestions about gifts in therapy (Borys & Pope, 1989;Freud, 1917Freud, /1963Gerson & Fox, 1999;Glover, 1955;Hundert, 1998;Knox et al, 2003;Kritzberg, 1980;Langs, 1974;Lewinsky, 1951;Pope et al, 1987;Ruth, 1996;Simon, 1989;Spandler et al, 2000;Talan, 1989), Dr. E reportedly did not address Emma's motivations for giving the gifts, the nature of what they communicated, the prominent role they began to take in her therapy, nor their effect on the therapy process and relationship. Perhaps, following a more intersubjectivist approach (e.g., Atwood & Stolorow, 1984;Hahn, 1998;Stolorow & Atwood, 1996), Dr. E may have sought to affirm and accept Emma by accepting her gifts (although we cannot know this without having talked to the therapist).…”
Section: Many-gift Examplementioning
confidence: 99%
“…In his study of 29 practicing British psychoanalysts, Glover (1955) found that none of the respondents accepted large gifts or money offerings, most did "not receive gifts gladly" (p. 319), and most analyzed patients' motives for giving gifts, hoping to reduce such behaviors in the future. In a survey of members of the American Psychological Association's Division 29 (Psychotherapy), Pope, Tabachnick, and Keith-Spiegel (1987) and Borys and Pope (1989) found that therapists almost universally accepted gifts of minimal financial value (e.g., less than $5) and rarely accepted those of higher value; they usually considered the former ethical and the latter unethical. Gerson and Fox (1999) surveyed 600 forensic professionals (MA, MD, MSW, PhD, PsyD) whose work demanded familiarity with the law (e.g., civil, competency, criminal, custody, workplace); respondents disapproved either somewhat or absolutely of five types of gifts (e.g., food, tickets to an event) and were neutral toward accepting a cupcake on a patient's birthday.…”
Section: Empirical Literature On Gift Givingmentioning
confidence: 99%
“…Although psychiatrists are three times as likely as psychotherapists to be sued for this kind of malpractice (Perr, 1989), epidemiological studies tend to suggest that there is no difference in rates between the different types of professional engaged in psychotherapy (Borys & Pope, 1989).…”
Section: The Extent Of the Problemmentioning
confidence: 99%
“…tickets to what type of event and at what value?). In addition, as was the case with Pope et al (1987) and Borys and Pope (1989), we do not know what types of clients these respondents had in mind when answering the questions.…”
mentioning
confidence: 99%